Corporate social responibility and its role in community development: An international perspective - Ismail, Maimunah (The Journal of International Social Research, 2009)
Corporate social responsibility (CSR) refers to strategies corporations or firms conduct their business in a way that is ethical, society friendly and beneficial to community in terms of development. This article analyses the meaning of CSR based on some theories available in literature. It is argued that three theories namely utilitarian, managerial and relational theories of CSR supported by works of other scholars in the area could be used to suggest that CSR becomes an international concern due to globalized nature of business that knows no border. CSR is evolving in its meaning and practice. The article then discusses the role of CSR in community development because the very logic of CSR is towards seeing its impact in community socially, environmentally and economically. Competencies required by CSR managers are also analyzed in order to have a better understanding of the practical aspects of CSR. Finally, conclusions and implications for future research are discussed.